Using a Calendar and Explanatory Instructions to Aid Within-household Selection in Mail Surveys. Issue 1 (February 2016) - Stange, Mathew; Smyth, Jolene D.; Olson, Kristen
Although researchers can easily select probability samples of addresses using the U.S. Postal Service's Delivery Sequence File, randomly selecting respondents within households for surveys remains challenging. Researchers often place within-household selection instructions, such as the next or last birthday methods, in survey cover letters to select respondents. Studies show that up to 30% of selections are inaccurate and samples tend not to represent key demographics. This article tests two design elements—a calendar and explanatory wording of selection instructions in cover letters—to aid and motivate households to carry out selection procedures accurately. We empirically examine these elements in two mail surveys of Nebraskans—the 2012 Nebraska Annual Social Indicators Survey and 2013 Nebraska Trees and Forest Survey. We find that neither the calendar nor the explanatory wording adversely affected response rates but that neither improved the representativeness of the completed samples and that the calendar actually reduced selection accuracy.